Το έργο του Τούρκου χρονικογράφου Ασίκ-πασά Ζαδέ (c. 1400-c. 1486) ως πηγή της υστεροβυζαντινής και πρώιμης Οθωμανικής περιόδου - Σαββίδης Αλέξης Γ.Κ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1982)
Aik-Paa-Zade (c. 1400 - c. 1486), the oldest and —perhaps— the most important among the early Ottoman (Osmanli) chroniclers, composed the «Tevarih-i Al-i Osman» (Chronicle of the House (=Dynasty) of Osman), a lengthy (166 chapters) account of early Turkish history from the early 13th century until the late 1450s, following the capture of Constantinople (Istanbul) by the sultan Mohammed (Mehmet) II «Fatih> (the «Conqueror») on 29 May, 1453. The importance of this authentic work is immense, since it includes — among others— a comparatively trustworthy (though sometimes impregnated by fable and legend) account of the arrival of the early Osmanlis in Anatolia, following their repulsion from inner Asia by the Mongols. It also contains valuable pieces of information on the gradual expansion of the Ottoman Sultanate in Asia Minor and the Balkan peninsula in the course of the 14th and 15th centuries, as well as important details on the policy pursued by the Conqueror concerning his Christian subjects. Several manuscripts of the chronicle’s old Ottoman script (in Arabic characters) survive in museums and libraries in Turkey (Top Kapi), and its first ed. by Ali Bey (Istanbul 1914) was followed by two more in the reformed latinized Turkish alphabet by F. Giese (Leipzig 1929) and Ç. N. Atsiz (Istanbul 1949), while a German translation (with commentaries) of the chronicle by R. F. Kreutel appeared in 1959 (Graz-Vienna).